2005
DOI: 10.1161/01.str.0000169947.08972.4f
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical Aphasia

Abstract: Background and Purpose-Very few neuroimaging studies have focused on follow-up of subcortical aphasia. Here, overt language production tasks were used to correlate regional cerebral blood flow (rCBF) changes and language performance in patients with vascular subcortical lesions. Methods-Seven aphasic patients were scanned twice with positron emission tomography (PET) at 1-year interval during a word-generation task. Using SPM2, Language-Rest contrast at PET1 was correlated to language performance and to time-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Although the BG are bilaterally involved in word generation, the left pre-SMA-BG ventral anterior thalamic loop has a role in word retrieval from lexical stores whereas the right BG have an inhibitory effect on the right frontal regions to prevent interference on language production (Crosson et al, 2003). Importantly, verbal fluency deficits were the most common impairment observed at 1 year, which supports the initial findings of de Boissezon et al (2005) revealing that executive language recovery as measured by a word generation task was not fully completed at 1 year post stroke.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although the BG are bilaterally involved in word generation, the left pre-SMA-BG ventral anterior thalamic loop has a role in word retrieval from lexical stores whereas the right BG have an inhibitory effect on the right frontal regions to prevent interference on language production (Crosson et al, 2003). Importantly, verbal fluency deficits were the most common impairment observed at 1 year, which supports the initial findings of de Boissezon et al (2005) revealing that executive language recovery as measured by a word generation task was not fully completed at 1 year post stroke.…”
Section: Discussionsupporting
confidence: 80%
“…Semantic fluency tests are sensitive to frontal lobe dysfunction after either left or right cortical injury (Baldo & Shimamura, 1998). Yet, impaired performance in tests measuring verbal fluency and word generation has also been reported in patients with BG stroke (de Boissezon et al, 2005;Kuljic-Obradovic, 2003;Mega & Alexander, 1994;Radanovic et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal neuroimaging studies on groups of patients have also been carried out to determine the neural mechanisms that are involved at different stages of the recovery process both in cortical (Heiss et al, 1999) and subcortical structures (de Boissezon et al, 2005). The study by Heiss et al (1999) demonstrated initial right hemisphere recruitment at two weeks post-stroke with a shift to perilesional regions at eight weeks.…”
Section: Stages Of Recoverymentioning
confidence: 99%
“…Perilesional activity has been associated with a good recovery (Heiss et al, 1999) as has bilateral activation (Cardebat et al, 2003;de Boissezon et al, 2005). The benefits of other mechanisms such as right hemisphere homologues are less clear.…”
Section: Stages Of Recoverymentioning
confidence: 99%
See 1 more Smart Citation